2003
DOI: 10.1080/03071375.2003.9747361
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Biostimulants on Growth and Vitality of Three Urban Tree Species Following Transplanting

Abstract: Four commercially available, biostimulants sold under the trade names 'Generate', 'Crop Set', 'Fulcrum' and 'Redicrop 2000' were applied either as a root drench or foliar spray to three transplant-sensitive tree species, red oak (Quercus rubra), birch (Betula pendula) and beech (Fagus sylvatica) post transplanting. The short and long-term efficacy of the biostimulants on growth was quantified by recording root and shoot vigour at week 8 and 20. In addition, improvements in tree vitality were assessed by measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…The chlorophyll a fluorescence-derived parameters have been used for evaluating the vitality of transplant-sensitive tree species after transplanting, and the effects ohe effects of biostimulants application, that increased leaf functionality as shown by higher values of PI (Fraser and Percival, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…The chlorophyll a fluorescence-derived parameters have been used for evaluating the vitality of transplant-sensitive tree species after transplanting, and the effects ohe effects of biostimulants application, that increased leaf functionality as shown by higher values of PI (Fraser and Percival, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll a fluorescence parameters have widely demonstrated that plants treated with biostimulants are less affected by a range of different biotic and abiotic stresses (Fraser & Percival 2003;Amanda et al 2009). Polysaccharides and oligosaccharides are other important biostimulant components that affect plant physiology.…”
mentioning
confidence: 99%
“…This observation is supported by [31] who asserted that biofertilizers worked to increase plant nutrient uptake and improve the nutrient use efficiency; and that there were no advantages in the use of sole biofertilizers in the promotion of plant growth [32]. However, the selection of appropriate biofertilizer according to [33] is therefore critical as growth effect could vary widely based on the different active organisms used in the formulation of the products. Studies by [34] showed inhibited root growth as resulted from low P supplied, whereas, [35] reported that in P-deficient plants, shoot growth was found to be more affected than root growth due to assimilate partitioning towards the root which led to a decrease in the shoot: Root dry matter ratio.…”
Section: Dry Matter Productionmentioning
confidence: 90%